An estimate of maintenance efficiency in Brown-Proschan imperfect repair model with bathtub failure intensity - Makram Krit; Abdelwaheb Rebai (Journal of Industrial Engineering and Management (JIEM), 2012)
Purpose: Estimate the maintenance efficiency in the Brown-Proschan model with the bathtub failure intensity. Design/methodology/approach: Empirical research through which we propose a framework to establish the characteristics of failure process and its influence on maintenance process. Findings: The main contribution of the present study is the reformulation of the Brown and Proschan model using the bathtub failure intensity .Practical implications: Our model is defined by BP reformulation one using bathtub failure intensity. This form of intensity is presented like superposition of two NHPP and Homogeneous Poisson one.Originality/value: This is the follow on research on the study that employed the power-law-process type of failure intensity.
Keywords: 650; repairable system; reliability; bathtub failure intensity; virtual age; imperfect maintenance; estimation; likelihood